Effect of Different Black Pepper Crop Ages on the Availability of Nitrogen, Phosphorus, and Potassium - Izzah Abd-Hamid; Wan Asrina Wan-Yahaya; Wan Mohd Razi Idris (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Black pepper cultivation at different land backgrounds and fertility can affect crop productivity. This study aims to determine soil-plant nutrients for three pepper farms based on crop ages and the correlation of selected physical and chemical properties. Samples were collected in Kapit, Bintulu, and Sri Aman and analyzed for physical and chemical properties. Soil nutrient in Bintulu (6 months old) has revealed higher soil pH (4.95) with higher Fe (0.21 g/kg) and N (1.33 g/kg) contents that is caused by burnt earth residue from the burning of secondary forest. Sri Aman (12 months old) showed greater TOC (3.34%), P (0.0032 g/kg), and K (0.10 g/kg) benefitted from a long year of cultivation and proper pre-establishment earlier. Nutrient removal is high in Bintulu for Fe, Mn, N, and K, while Sri Aman for P is due to early harvesting before its mature phase, whereby the increase in nutrient accumulation in leaves to support berries. Correlation has revealed the role of soil pH in governing the availability of TOC, P, and K. The increasing soil pH increases the availability of P and K.Â Hence, the availability of N, P, and K is affected by numerous reasons, such as pH and crop management.